Effect of modified feeding practice on milk production of cross bred dairy cows in Baghabari milk shed area, Sirajgonj - Rahman, Md Zillur; Ali, Md Yousuf; Sarker, NR; Afroz, MF; Rahman, MOA; Karim, MR (Asian Journal of Medical and Biological Research, 2015)
A research work was undertaken to find out alternative feeding practices for dairy cows in Baghabari milk shed areas. The trial was conducted in the village Alokdiar, Shajadpur, Sirajgonj. Twenty cross bred lactating dairy cows of 340 ±15.5 kg live weight were used for the trial. Animals were equally and randomly allocated dietary into four groups, T0 (Rice straw + concentrate), T1 (Napier silage + concentrate), T2 (Khesari hay + concentrate) and T3 (UMS + concentrate). There was no significant difference in total DM intake among the four groups. The DCP (kg/d) intake was significantly (P<0.01) differ among the treatment group. The highest DCP (kg/d) intake was observed in T2 (0.824) followed by T1 (0.739), T3 (0.707) and T0 (0.510). Higher CP content in Khesari hay which reflected DCP intake. The ME (MJ/d) intake was also significant (P<0.05) difference among the dietary groups. ME (MJ/d) was the highest 93.46 in T2 afterward 92.21 in T3 and lowest 77.56 in T0. The average milk yield (l/d) was the highest in T2 (10.76) followed by T3 (10.13), T1 (9.86) and T0 (7.31), respectively. Apparent digestibility were significant (P<0.05) variation among the dietary groups of animals in case of DM, OM and CP. The highest DM digestibility was observed in T2-Khasari based diet (74.00±1.54) followed by T3-UMS (73.11±1.33), T1-Napier silage (70.00±1.23) and T0-rice straw (53.00±0.97) based diet, respectively. Introduction of legume hay as modified feeding practice may be an alternative feeding system to sustain milk production during lean period. Asian J. Med. Biol. Res. June 2015, 1(2): 254-258